Influence to Inspire (I2I) – a novel diabetes peer support program - Mohamed Shah, Fatimah Zaherah; Wan Muhamad Hatta, Sharifah Faradila; Eddy Warman, Nur ‘Aini Eddy Warman; Zainordin, Nur Aisyah; Awang, Mohd Hazriq Awang; Mohamad, Aimi Fadilah; Abdul Ghani, Rohana (Universiti Teknologi MARA, Sarawak, 2022)
Diabetes Mellitus (DM) is a chronic disease with many complications, necessitating the need for effective long-term control of this condition. Diabetes self-management is an important aspect of management, and dissemination of information through peer-support groups can improve positive behaviour pattern in self-management. At this moment, a practical peer-support group for diabetic patients in Malaysia is currently not available, but is a critical requirement in improving patient education and self-empowerment. Therefore, the objective of this study is to provide comprehensive knowledge to influencers regarding diabetes and its complications, as well as aiming to equip the influencers with confidence and skills to disseminate this knowledge to a larger group of patients with DM. An Innovative Program was introduced - A novel diabetes peer support patient education program designed to impart knowledge in an engaging manner. This program was divided into five main modules, each covering the more important aspects of diabetes, with specific targeted learning outcomes. Module 1 introduced the program, followed by a talk on motivational skills, and interactive lecture on important aspects of diabetes. Module 2 focused on more specific DM treatment, with hands-on experience followed by a session on exercise with certain techniques demonstration. Module 3 concentrated on complications of DM with lecturers, case-based scenario and experience-sharing, and ended with interactive games. Module 4 emphasized on healthy food choices in DM, with quizzes and cooking demonstration. Module 5 consolidated information provided during the program, followed by a session on psychological aspects of diabetes with role-play, and ended with a goal-setting activity. This program provided comprehensive information on diabetes and its management, and equipped influencers with the ability to disseminate the knowledge, aiming to improve patient self- management and empowerment in controlling diabetes, hence has a huge impact in reducing complications and co-morbidities associated with DM.